Natural source electromagnetic survey for geothermal application in industrial area with strong electromagnetic noise - Guo, Rongwen; Xue, Peng; Liu, Jianxin; Wang, Yongfei; Tian, Shengqi; Li, Jianjian; Xue, Wei (Frontiers in Energy Research, 2024)
The magnetotelluric (MT) method is a widely used geophysical technique for deep structure exploration. However, rapid industrial development has resulted in significant anthropogenic interference for practical applications of this method in recent years. To carry out MT survey in regions with strong electromagnetic (EM) noise, we develop a strategy, in which part of MT sites are set for night time period and a newly proposed automatic clustering method based on MT signal patterns is applied to process measured data from Yingde area in Guangdong. The MT sites are employed in night time to avoid human activity and measure the quiet time MT signal to make sure that we can capture portion of MT signal. Based on cosine similarity, we can use clustering algorithms to separate the signals from the noise. The application of this strategy for geothermal exploration in Yingde area in Guangdong, indicates the validity of our proposed strategy for real geothermal detection.